Pelayanan Haji Furoda Di Travel Jannah firdaus - Biben, Rizaldi Ahmad; Muhtarom, Mumuh (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2024)
The aim of this research is to find out what the concept of furoda hajj services is at PPIU Jannah Firdaus, what the furoda hajj service strategy is at PPIU Jannah Firdaus, and what are the inhibiting and supporting factors for furoda hajj services at Travel Jannah Firdaus. The method used in this research uses a descriptive method with a qualitative approach and data collection techniques through observation, interviews and documentation. The results of this research show that the PPIU Jannah Firdaus Furoda Hajj service tries to provide a good Furoda Hajj experience for the congregation, provides comfort in worship, and is committed to providing the best service. The strategy used for Furoda Hajj services is to provide discounts but by providing the best facilities as per the package provided. Inhibiting factors include changing regulations, changes in congregation schedules, global conditions, and intense competition between travelers.